Temporal changes in phytoplankton structure and composition at the Turkwel Gorge Reservoir, Kenya - Kotut, Kiplagat; Krienitz, L.; Muthuri, Francis M. (Kluwer Academic Publishers, 1998)
Temporal changes in phytoplankton chlorophyll a, composition, diversity, biomass (density and fresh weight) and primary production were investigated at the Turkwel Gorge Reservoir (Kenya) over a two year period (1994 and 1995). The phytoplankton properties investigated revealed a seasonal pattern that was very distinct in 1994 and muted in 1995. The wet season was characterized by higher levels of chlorophyll a, biomass and primary production and a lower diversity. A prominent seasonality in 1994 was found to be the result of a higher river inflow volume as compared to 1995. Chlorophyll a changes showed some positive correlation to changes in total nitrogen and total phosphorus. Diversity changes were inversely correlated to changes in total counts (R = −0.84 and −0.96 for 1994 and 1995 respectively). Individual species density changes varied from a distinct seasonal pattern to a nearly uniform density. While the diatom Achnanthes dominated the wet season in 1994, coccoid blue green algae were dominant during most of 1995. Throughout the study period, most biomass was due to the diatoms but with a lower percentage of total biomass in 1995 (40%) as compared to 1994 (88%). The wet season biomass in each year was dominated by the diatoms. Dominance of the intervening period changed irregularly between diatoms, dinoflagellates, green algae and blue green algae. The range of variation in chlorophyll a, total biomass and primary production were; 4.9 to 36.8 µg l-1, 440.14 to 11172.70 mg m-3 and 1.85 to 9.67 g O2 m-2 d-1 in 1994 and 4.9 to 11.5 µg l-1, 486.46 to 1351.39 mg l-1 and 3.08 to 5.41 g O2 m-2 d-1 in 1995 in the same order.
Keywords: reservoir; phytoplankton; diversity; primary production; seasonality